Kvinder og andre dæmoner - Singhalesiske kvindebilleder i myter og ritualer - Andersen, Grethe Schmidt (Religionsvidenskabeligt tidsskrift, 1986)
Singhalese Buddhism in it popular form associates female identity and the life-threatening forces symbolized as demons. Demons (yakku) are low and polluted beings, persecuting humans, and placed beneath the gods and Buddha in the lower part of the hierarchical pantheon of the Sinhalese. This article is concerned with the aspects of the demonic in its relationship to female identity, whose core in cultural definition is the female reproduction potentials connected with the concept of ritual pollution. On the basis of a myth on the constitution and development of the demon Gara Yaka it is shown that femininity in the myth is a metaphor of the excessive desire, which gives birth to suffering in the form of demons. In the ritual context, exemplified in this article by girl’s puberty ceremonials, femininity is defined by the pollution of menstruation. This enables the isolation of the dangers of fertility and its condition (desire) as specifically female. The concept pollution is found to be connected with the dialectic nature/culture relationship. Woman and her domain - the house - symbolizes this dialectic and are both foci of intense ritual activity. Sinhalese popular religion acknowledges that suffering connected with existence and its conditions is unavoidable, but it asserts the possibility of limiting and isolation suffering by making the symbol of suffering, desire and pollution (i.e. the women) ritually controllable.